Maingot's abdominal operations - Zinner, Michael; Ashley, Stanley W; Hines, O. Joe (McGraw-Hill, 2018)
The definitive full-color illustrated guide to abdominal operations for general, colorectal, and gastrointestinal surgeons.
Keywords: chirurgie trávicího traktu; Abdomen; chirurgie; Surgical Procedures, Operative; břicho; Digestive System Surgical Procedures; chirurgie operační; miniinvazivní chirurgické výkony; Minimally Invasive Surgical Procedures